2008
DOI: 10.1149/1.2952807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gallium Nitride Grown on Patterned Sapphire Substrate with Shallow U-Shaped Stripe Grooves

Abstract: A patterned sapphire substrate with shallow U-shaped stripe grooves along the ͗112 ¯0͘ direction prepared by chemical wet etching was used for the growth of high-quality gallium-nitride-based epilayers without air gap formation. From characterization by scanning electron microscopy, transmission electron microscopy, and micro-photoluminescence, it was determined that the crystalline and optical qualities of gallium-nitride-based epilayers grown on the groove region are better than those on the ridge region. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[11][12][13][14][15][16] On the other hand, the patterns on the PSS can reduce the threading dislocations in the GaN epitaxial layers owing to the possible lateral growth of the GaN epi-layer. 2,5,6,8,17 Some recent studies indicated that the use of nano-scale patterned sapphire substrate leads to increase in IQE, which is resulted from the significant reduction in the threading dislocation density (two-orders of magnitude reduction) and reduction in the fraction of the screw dislocation density. [18][19][20][21] Besides, some researchers also indicate that IQE can be improved by QW designing (for examples, non-polar QW and large overlap QW).…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] On the other hand, the patterns on the PSS can reduce the threading dislocations in the GaN epitaxial layers owing to the possible lateral growth of the GaN epi-layer. 2,5,6,8,17 Some recent studies indicated that the use of nano-scale patterned sapphire substrate leads to increase in IQE, which is resulted from the significant reduction in the threading dislocation density (two-orders of magnitude reduction) and reduction in the fraction of the screw dislocation density. [18][19][20][21] Besides, some researchers also indicate that IQE can be improved by QW designing (for examples, non-polar QW and large overlap QW).…”
mentioning
confidence: 99%
“…Meanwhile, high quality c-plane GaN epitaxial layers with low dislocation densities can be achieved on maskless c-plane patterned sapphire substrates ͑PSSs͒ with periodic grooves or holes. [11][12][13] In comparison with the conventional epitaxial lateral overgrowth technique, the photolithography and epilayer growth process are simplified, and the contamination from the dielectric mask is prevented. In addition, the geometrical effect of patterned substrates can also effectively enhance light extraction, improving the optoelectronic device performance and efficiency.…”
mentioning
confidence: 99%
“…where C 2 is the concentration of nitrogen dimers, g 1 and g 2 are the numbers of available sites per unit cell for the monomer and dimer, respectively, ⍀ 0 is the volume of a unit cell, ⌬G 2 is the binding energy of the dimer, and D 1 and D 2 are the monomer and dimer diffusivities, respectively. 36 If the dimer is immobile ͑i.e., neglecting D 2 ͒, then a generalized expression for the nitrogen monomer diffusivity can be substituted into Eq. 2 to give…”
Section: Discussionmentioning
confidence: 99%